EVALUATION OF ANTI-GLYCATION EFFECT AND SAFETY OF SERUM ANTI-AGING FORMULATION CONTAINING GOLD NANOPARTICLES (AUNP) USING SIDAGURI EXTRACT (SIDA RHOMBIFOLIA) - WALUYO, DYAH AYUWATI; SUTRIYO (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study is to determine the anti-aging properties and safety of serum containing gold nanoparticles (AuNP) using Sidaguri extract (Sida rhombifolia) through their anti-glycation effect. Methods: The anti-aging effect of serum was performed in vitro by measuring advance glycation end products (AGEs) formed during incubation using a Microplate reader, and safety of serum was performed using hen’s egg chorioallantoic membrane (HET-CAM) method using White Leghorn egg. Results: The study showed that serum formulation had an anti-glycation effect with inhibition percentages are 68.20±6.86% and 74.83%±19.91% for a serum containing 10% and 20% gold nanoparticles and little to no irritation potency for both serum formulations with RI value 0.0 and 0.0, respectively. Conclusion: Due to both their anti-glycation effect and irritation behavior, serum formulation containing gold nanoparticle synthesized using Sidaguri extracts could be utilized as anti-aging cosmetics in the future.